Non-Ischemic Myocardial Fibrosis in End-Stage Kidney Disease Patients: A New Perspective - Kenji Nakata; Nobuhiko Joki (MDPI AG, 2023)
Cardiovascular medicine, especially for ischemic heart disease, has evolved and advanced over the past two decades, leading to substantially improved outcomes for patients, even those with chronic kidney disease. However, the prognosis for patients with end-stage kidney disease (ESKD) has not improved so greatly. Recent studies have reported that myocardial fibrosis in chronic kidney disease patients is characterized by patchy and interstitial patterns. Areas of fibrosis have been located in the perivascular space, and severe fibrotic lesions appear to spread into myocardial fiber bundles in the form of pericellular fibrosis. These findings are fully consistent with known characteristics of reactive fibrosis. In hemodialysis patients, a greater extent of myocardial fibrosis is closely associated with a poorer prognosis. In this review, we focus on non-ischemic cardiomyopathy, especially reactive myocardial fibrosis, in ESKD patients.